Model-independent measurement of the W-boson helicity in top-quark decays at D0 - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2008)
We present the first model-independent measurement of the helicity of W bosons produced in top quark decays, based on a 1fb-1 sample of candidate tt̄ events in the dilepton and lepton plus jets channels collected by the D0 detector at the Fermilab Tevatron pp̄ Collider. We reconstruct the angle θ* between the momenta of the down-type fermion and the top quark in the W boson rest frame for each top quark decay. A fit of the resulting cos θ* distribution finds that the fraction of longitudinal W bosons f0=0.425±0.166(stat)±0.102(syst) and the fraction of right-handed W bosons f+=0.119±0.090(stat)±0.053(syst), which is consistent at the 30% C.L. with the standard model. © 2008 The American Physical Society.